Prevalence of hepatitis B virus and hepatitis C virus co-infection in human immunodeficiency virus positive patients: a study from tribal area of central India - Khunte, Prakash; Khare, R. L.; Beck, P.; Kumar, Sanjeev (International Journal of Research in Medical Sciences, 2017)
Background: AIDS was first recognized in the United States in 1981, in homosexual men in New York. In 1983, human immunodeficiency virus (HIV) was isolated from a patient with lymphadenopathy, and by 1984 it was shown that causative agent of AIDS. Human immunodeficiency virus (HIV), hepatitis B virus (HBV), and hepatitis C virus (HCV) are major public health concerns. Because of shared routes of transmission, HIV HCV co-infection and HIV-HBV co-infection and/or both are common. HIV-positive individuals are a risk of co-infection with HBV and HCV and/or both infections. Co-infections of HBV and HCV with HIV have been associated with reduced survival, with an increased risk of progression to severe liver diseases and an increased risk of hepatotoxicity associated with antiretroviral therapy. Methods: The present study was conducted duration from September 2011 to October 2013. A total of 100 AIDS patients of different age groups including 68 males and 32 females were enrolled in the study attending outdoor or admitted in wards of Department of Medicine, Dr. B. R. A. Hospital Raipur (C.G.). 50 HIV negative healthy controls are also included in the study to minimize the observer and instrumental bias. Results: In our study most common occupation of patients were 24 (24 %) labour. Most common mode of transmission was heterosexual seen in 93 (93%) of patients. The prevalence of HbsAG in HIV seen in 6 (6%) of cases .The prevalence of HCV in HIV seen in 2 (2%) of cases and all patients were male and found to be age group between 30-40 year The co-prevalence of HbsAG & HCV in HIV seen in 1 (1%) of cases and it was female patient and age group was 30 to 40 years. There is incidence of deranged liver function tests in HBsAg for S. Bilirubin, SGOT, SGPT and alkaline phosphatase was 6, 4, 3 and 2 patients respectively in HCV SGOT in 1 patients. The incidence of deranged liver function tests was 5 among the co-infected patients with CD4<200 compared to 2 in those with CD4>200. The mean CD4 count was 193.6 /mm. Maximum patient seen in grade 1 (88.8 %) liver enzyme elevation. Most common opportunistic infection in both HBsAG & HCV were pulmonary tuberculosis. Conclusions: Prevalence of hepatotoxicity is more common in HIV patient than other & co prevalence of either HBsAG or HCV accelerates the progression of liver disease which further causing liver derangement and increase morbidity & mortality of the patients. Mild to moderate hepatotoxicity is common as compared to severe hepatotoxicity. Screening of HIV with HBsAg & HCV and early diagnosis & treatment of disease will decrease the morbidity and mortality of the patients.